Work gains and strains on father involvement: The mediating role of parenting styles - Diniz, E. (2023)
The balance between work and family demands is one of the main challenges of contemporary parenting. However, most of the research has focused on mothers’ perspectives, with fathers’ perspectives about the links between work–family activities and father involvement, as well as the role of indirect effects, such as parenting styles, being less explored. This study aims to bridge these gaps by exploring whether work strains or gains are related to father involvement in childcare and the mediating role of parental styles, focusing on fathers’ reports. Working, married fathers of preschoolers (n = 411) self-reported about work strains and gains, parental styles, and father involvement. Structural equation modeling, using maximum-likelihood estimation, provided good fit indices. Results of the bootstrap analysis revealed how fathers’ gains indirectly increased involvement both in direct and indirect care through positive parental styles. Otherwise, fathers’ strains at work had a negative indirect effect on direct care through negative parental styles. Findings contribute to work–family interface by showing how parental styles account for mediating environmental challenges on father involvement.